Competitive positioning of tourism academic knowledge. (August 2022) - Schweinsberg, Stephen; Sharpley, Richard; Darcy, Simon
Abstract: For more than 75 years tourism academia has evolved from humble beginnings in catering and hospitality degrees to become an institutionalised and global knowledge creation sector. Over the last 18 months, however, the COVID-19 pandemic has had the effect of amplifying concerns amongst some in government and industry over the role of tourism academia in the industry's future. This article employs Porter's Five Forces Model to review the forces impacting on the competitive positioning of tourism academic knowledge.